Beta-carotene content and quantity and quality of squash-banana catsup - Lozada, Ma. Aurora Melchora D.; De Leon, Sonia Y. (1992.)
Catsup that has 592.05 micrograms per 100 grams of provitamin A activity was developed from fully ripe "lagkitan' squash (Cucurbita maxima) and "saba" bananas "Musa sapientum). The recipe of the Food and Nutrition Research Institute (FNRI) for catsup making was modified to adapt it for squash-banana catsup. Three experimental ratios of squash-banana catsuo were developed based on the modified FNRI recipe in Phase II. pH percentage titratable acidity, and soluble solids content of the experimental samples along with a commercial standard sample were determined. Viscometric measurements were also performed by using the Brookfield Synchro-electric Viscometer. A panel evaluation was conducted to determine the subjective acceptability of the product. The experimental sample which then exhibited the best quality control characteristics and which proved to be better than the commercial sample was the sample coded 640 (60% squash and 40% banana). It had a pH value of 4.3, T.A. = 1.24 % and 30.1°Brix soluble solids. Panel mean scores indicated that the panelists perceived sample 640 as having a brownish red color, slightly catsup odor, sweet-sour-spicy flavor, and a slightly smooth texture. This sample averaged 6.66 for its general acceptability, which was a score equivalent to "like moderately". The beta-carotene content of sample 640 was determined by the colorimetric method in the third phase.
Thesis (BSFT)--University of the Phlippines Diliman.
Keywords: Ketchup